2002
DOI: 10.1086/342654
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetically Torqued Disk Model for Be Stars

Abstract: Despite extensive study, the mechanisms by which Be star disks acquire high densities and angular momentum while displaying variability on many timescales are still far from clear. In this paper, we discuss how magnetic torquing may help explain disk formation with the observed quasi-Keplerian (as opposed to expanding) velocity structure and their variability. We focus on the effects of the rapid rotation of Be stars, considering the regime where centrifugal forces provide the dominant radial support of the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 38 publications
2
105
2
Order By: Relevance
“…The material is expelled from the central star and placed in a thin equatorial disk with Keplerian rotation (Meilland et al 2007). Different mechanisms such as rapid rotation (Porter 1996;Townsend et al 2004;Domiciano de Souza et al 2003;Frémat et al 2005), mass loss from the stellar wind (Stee & de Araujo 1994;Bjorkman & Cassinelli 1993;Curé 2004;Silaj et al 2014a), binarity (Okazaki et al 2002;Romero et al 2007;Oudmaijer & Parr 2010), magnetic fields (Donati et al 2001;Cassinelli et al 2002;Neiner et al 2003), and stellar pulsations (Rivinius et al 2003) have been proposed to explain how the star loses enough mass to form the CE and how this material is placed in orbit, but it seems that more than one mechanism is required to reproduce the observations. Such mechanisms must continually supply enough angular momentum from the star to form and to maintain the disk.…”
Section: Introductionmentioning
confidence: 99%
“…The material is expelled from the central star and placed in a thin equatorial disk with Keplerian rotation (Meilland et al 2007). Different mechanisms such as rapid rotation (Porter 1996;Townsend et al 2004;Domiciano de Souza et al 2003;Frémat et al 2005), mass loss from the stellar wind (Stee & de Araujo 1994;Bjorkman & Cassinelli 1993;Curé 2004;Silaj et al 2014a), binarity (Okazaki et al 2002;Romero et al 2007;Oudmaijer & Parr 2010), magnetic fields (Donati et al 2001;Cassinelli et al 2002;Neiner et al 2003), and stellar pulsations (Rivinius et al 2003) have been proposed to explain how the star loses enough mass to form the CE and how this material is placed in orbit, but it seems that more than one mechanism is required to reproduce the observations. Such mechanisms must continually supply enough angular momentum from the star to form and to maintain the disk.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, considering the analysis of X-ray observations of magnetic O stars, it appears that only one star, θ 1 Ori C, displays properties that are fully compatible with the predictions of the MCWS model. Cassinelli et al (2002) and Brown et al (2008) studied the case of fast rotating magnetic massive stars, specifically addressing the formation of disks in classical Be-type stars. They showed that magnetic torquing and channeling of wind flow from intermediate latitudes of the stellar surface can, for plausible field strengths, create a dense disk a few stellar radii in extent.…”
Section: Magnetic Fields On Massive Stars Are Not Necessarily Manifesmentioning
confidence: 99%
“…Let us next examine the nature of magnetic channeling for the winds from rotating hot stars, with particular emphasis on whether a large-scale magnetic field could spin-up the stellar wind outflow into a "Magnetically Torqued Disk" (MTD), as advocated by Cassinelli et al [21]. As noted above, MHD simulations [24,25] indicate that a dipole magnetic field can confine the flow within closed loops that extend out to about the Alfven radius, R A ≈ η 1/4 * R * .…”
Section: Wind Spin-up From Dipole Aligned With Stellar Rotation Axismentioning
confidence: 99%
“…The next section applies MHD simulations of a Magnetically Confined Wind Shock (MCWS) model developed [18,19] to explain X-ray emission observed by Rosat [20] from the magnetic O7V star θ 1 Ori C. We then discuss the role of magnetic fields in spinning up the wind outflow from a rotating star, emphasizing that this does not produce the Magnetically Torqued Disk (MTD) proposed [21] as a mechanism for producing the orbiting, Keplerian disks inferred from the characteristic Balmer line emission in Be stars. We next show however that the very strong magnetic fields of Bp stars can lead to a Rigidly Rotating Magnetosphere (RRM) [22], with rigid-body disks or clouds that can explain quite well the observed emission in Bp stars like σ Ori E. We further show that the eventual centrifugal breakout of such material can lead to strong heating from magnetic reconnnection, which thus could explain the very hard X-ray flares seen from this star.…”
Section: Introductionmentioning
confidence: 99%